2021
DOI: 10.7759/cureus.19747
|View full text |Cite
|
Sign up to set email alerts
|

Real World Utilization of Bamlanivimab at a Rural Community Hospital

Abstract: Introduction Although there were several proposed treatments for patients that were hospitalized with COVID-19, outpatient treatments for those with mild to moderate illness were limited prior to the emergency use authorization (EUA) of virus-neutralizing monoclonal antibodies. To assess the efficacy of outpatient monoclonal therapy, the investigators assessed the seven, 14, and 28-day emergency department and hospitalization rates of adult patients given bamlanivimab for the treatment of COVID-19 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The COVID variants of interest in the studies included 21C (Epsilon), 20E (EU1), and B.1.1.7 (Alpha). Seven additional studies were identified in January 2023, and these were included in our analysis ( Chilimuri et al, 2022 ; Cooper et al, 2021 ; Iqbal et al, 2021 ; Leavitt et al, 2021 ; Murillo et al, 2022 ; Rainwater-Lovett et al, 2021 ; Rubin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The COVID variants of interest in the studies included 21C (Epsilon), 20E (EU1), and B.1.1.7 (Alpha). Seven additional studies were identified in January 2023, and these were included in our analysis ( Chilimuri et al, 2022 ; Cooper et al, 2021 ; Iqbal et al, 2021 ; Leavitt et al, 2021 ; Murillo et al, 2022 ; Rainwater-Lovett et al, 2021 ; Rubin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Avoidance of public programs for fear of harming their immigration status was reported by Hispanic immigrants which coincided with a 2x increased delay of needed medical care 30 . This could have led to decreased utilization of COVID-19 monoclonal antibodies leading to increased hospitalization rates secondary to uninhibited viral replication [31][32][33] . Institutional disenfranchisement may further underly this reluctance as Arizona proposed vaccine policies prioritizing U.S. citizens and legal residents, a significant obstacle for undocumented Hispanics seeking protection with the COVID-19 vaccine 25 .…”
Section: Discussionmentioning
confidence: 99%